PERTANGGUNGJAWABAN PIDANA DALAM KASUS CYBERBULLYING ANALISIS YURISPRUDENSI DAN IMPLEMENTASI KUHP NASIONAL 2023 SERTA UU ITE - Ahmad Fahrul Rozi; Siti Humulhaer; Ani Wahyuni; Regina Yura Fitriah Sari; Oky Rona Wijaya (CV. Lafadz Jaya, 2026)
Cyberbullying has become a serious challenge in the digital era in Indonesia, with an alarming prevalence. Data from the Indonesian Child Protection Commission recorded 1,478 cases of bullying (both online and offline) in 2023, with significant psychological impacts that in some cases have led to suicide. This study analyzes the criminal liability of cyberbullying perpetrators from the perspective of the Indonesian National Criminal Code 2023, which will come into effect on 2 January 2026, and Law Number 1 of 2024 on Electronic Information and Transactions. Using a normative analytical juridical research method, this study examines the harmonization between the National Criminal Code as lex generalis and the ITE Law as lex specialis, as well as the shift in sentencing paradigms from a retributive approach toward a restorative one. The findings indicate that the National Criminal Code provides a stronger foundation for the enforcement of cyberbullying laws through the regulation of supervisory penalties, the application of restorative justice, and the strengthening of criminal sanctions. However, the main challenges remain the absence of a specific cyberbullying offense, the complexity of proving the element of “repetition,” and the anonymity of perpetrators in digital environments. This study recommends the establishment of a specific cyberbullying offense within the ITE Law and the development of law enforcement strategies that prioritize victim protection as well as the rehabilitation of offenders.